184k views
24 votes
Evaluate the function. g(x) = 3x^2 – 2x + 5 Find f(2)​

User Revoua
by
5.4k points

1 Answer

8 votes

Answer:

13

Explanation:

Replace X with 2

Evaluate the function. g(x) = 3x^2 – 2x + 5 Find f(2)​

g(x) = 3(2)^2 – 2(2) + 5

Next conduct PEMDAS

Exponents are first so solve 2^2 which is 2 x 2 = 4

g(x) = 3(4) – 2(2) + 5

Next step is multiplication multiply 3 x 4 and 2x2

g(x) = 12 – 4 + 5

conduct adding and subtracting left from right

g(x) = 13

User Prhmma
by
5.1k points